A high-sulfur iron concentrate pellet desulfurizer and a method for strengthening the desulfurization of high-sulfur iron concentrate pellets
By using a desulfurizer composed of direct reduction of iron powder dust, calcium peroxide powder and manganese dioxide powder in high sulfhydryl concentrate pellets, and optimizing the drying process, the problem of low desulfurization efficiency of high sulfhydryl concentrate pellets is solved, achieving efficient desulfurization and pellet quality improvement.
Patent Information
- Application Number
- CN202510018292.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The desulfurization efficiency of high sulfide concentrate pellets in the drying and preheating section is low, resulting in SO2 cycle enrichment, reducing the mass of the pellets and causing serious halo rings in the rotary kiln.
Desulfurization agent composed of direct reduction of iron powder dust, calcium peroxide powder and manganese dioxide powder is used to promote the desulfurization of the high-sulfur iron concentrate pellets through the oxidation and roasting process, and at the same time, the exhaust drying section is cancelled and the drying process is optimized to avoid SO2 enrichment.
The desulfurization efficiency of high sulfide concentrate pellets in the drying and preheating section is significantly improved, the sulfur content is reduced, the metallurgical performance is improved, and the knot in the rotary kiln is avoided, which improves the quality of the pellet ore.
Smart Images

Figure CN119433112B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a desulfurizer, in particular to a high-sulfur iron ore concentrate pellet desulfurizer, and also to a method for strengthening the desulfurization of high-sulfur iron ore concentrate pellets by using the desulfurizer, belonging to the technical field of iron ore pellet production. Background Art
[0002] With the development of the steel industry, the demand for iron ore concentrate is increasing, but the reserves of high-grade iron ore concentrate are gradually decreasing. Many steel companies regard the large-scale utilization of complex ores as the main direction of future development, including high-sulfur iron ore concentrate.
[0003] High-sulfur iron concentrate is an iron concentrate with a high sulfur content, in which sulfur is present in the form of pyrite / pyrrhotite. During the production of high-sulfur iron concentrate pellets, most of the pyrite / pyrrhotite quickly decomposes in the preheating section and releases SO2, which enters the flue gas. However, when the proportion of high-sulfur iron concentrate in the pellets is too high, the desulfurization rate of the pellets in the drying and preheating section needs to be increased. In addition, when pellets are produced using the chain grate-rotary kiln process or the belt roaster process, the high-temperature flue gas from preheating II is usually used as a heat source to dry the pellets in the extraction section. Therefore, the green balls that are not completely dried in the blast drying section continue to be dried and dehydrated in the extraction section to completely dry the pellets. When the high-temperature flue gas from preheating II is used to exhaust and dry the pellets, the SO2 in the flue gas quickly combines with water vapor to generate H2SO4, which further reacts with the alkali metal compounds on the surface of the pellets to form a layer of sulfate precipitation inside the pellets. When the pellets enter the rotary kiln, the easily decomposable sulfates quickly decompose and reduce the surface strength of the pellets. The friction during the movement of the pellets causes the surface powder of the pellets to fall off, resulting in serious ring formation in the rotary kiln. Summary of the invention
[0004] The aim is to address the technical issues in the production of pellets from high-sulfur iron ore, such as low desulfurization efficiency in the preheating and drying section, reduced pellet quality caused by SO2 circulation enrichment, and severe ring formation in the rotary kiln.
[0005] The first object of the present invention is to provide a high-sulfur iron ore concentrate pellet desulfurizer, which can enhance the desulfurization efficiency of the high-sulfur concentrate pellets in the drying and preheating stage, reduce the sulfur content in the iron ore pellets, and improve their metallurgical properties.
[0006] The second object of the present invention is to provide a method for enhancing the desulfurization of high-sulfur iron ore concentrate pellets. The method enhances the desulfurization by using a desulfurizer in the high-sulfur iron ore concentrate pellets. At the same time, the pellet drying process is optimized and the exhaust drying section is eliminated to avoid the raw balls from absorbing SO2 in the flue gas during the exhaust drying process, thereby preventing the formation of a sulfate crust on the surface of the pellets, thereby achieving the purpose of improving the quality of the pellets and preventing ringing in the rotary kiln.
[0007] In order to achieve the above technical objectives, the present invention provides a high-sulfur iron concentrate pellet desulfurizer, which is composed of the following components in mass percentage: direct reduced iron powder dust 85-93%; calcium peroxide powder 5-10%; manganese dioxide powder 2-5%.
[0008] During the oxidative roasting process, the calcium peroxide powder, direct reduced iron powder dust and manganese dioxide powder in the desulfurizer of the present invention increase the temperature field inside the high-sulfur iron concentrate pellets through complex oxidation heat release between the components, and at the same time catalyze the pyrite / pyrrhotite inside the high-sulfur iron concentrate pellets to accelerate the conversion and achieve desulfurization, thereby greatly improving the desulfurization efficiency. At the same time, the introduction of direct reduced iron powder dust can also increase the iron grade of the high-sulfur iron concentrate pellets, avoiding the technical problem of reduced iron grade of the iron ore pellets after the introduction of the desulfurizer.
[0009] The high-sulfur iron concentrate pellet desulfurizer of the present invention uses direct reduced iron powder dust as the main component, and calcium peroxide powder and manganese dioxide powder as secondary components, mainly to improve the desulfurization efficiency of pyrite concentrate pellets while ensuring a higher iron grade of the iron ore pellets.
[0010] As a preferred solution, the Fe content of the direct reduced iron powder dust is 50-80%, and the SiO2 content is 1.5-2.5%. Direct reduced iron powder dust has a high Fe content, and using it as the main component of the desulfurizer will not reduce the iron grade of the iron ore pellets.
[0011] As a preferred solution, the particle sizes of the direct reduced iron powder dust, the calcium peroxide powder and the manganese dioxide powder all satisfy that the mass proportion of the -10 μm particle size is more than 90%. The components in the desulfurizer maintain a relatively fine particle size, which can ensure that the raw ball strength will not be reduced, and are evenly distributed in the pellets, so as to better exert the desulfurization effect.
[0012] The present invention also provides a method for enhancing the desulfurization of high-sulfur iron concentrate pellets, which comprises mixing the desulfurizer with the sulfur-containing iron concentrate and a binder to form pellets, and sequentially performing blast drying, preheating I, preheating II and roasting on the obtained green balls using a chain grate-rotary kiln system to obtain finished pellets.
[0013] The method for enhancing the desulfurization of high-sulfur iron ore concentrate pellets provided by the present invention, on the one hand, introduces a special desulfurizer into the pellets, which can promote deep desulfurization of the raw balls during the drying and preheating process; on the other hand, the exhaust drying section is eliminated, and the blast-dried pellets directly enter the preheating section, so that sulfur dioxide is concentrated in the preheating section for removal, and the high-concentration sulfur dioxide flue gas in the preheating section is prevented from circulating into the exhaust drying process to enrich SO2 on the surface of the pellets, thereby improving the quality of the pellets and avoiding ringing in the rotary kiln.
[0014] As a preferred solution, the mass of the desulfurizer accounts for 1.0-2.5% of the total mass of the desulfurizer, the sulfur-containing iron concentrate and the binder. When the amount of desulfurizer added is high, the desulfurization efficiency of the high-sulfur iron concentrate can be improved, but the iron grade of the pellets will be reduced. Therefore, the appropriate amount of addition can simultaneously ensure the desulfurization efficiency and iron grade of the high-sulfur iron concentrate pellets.
[0015] As a preferred solution, the sulfide-containing iron concentrate has a TFe content of 58% to 66% by mass and a sulfur content of 0.5% to 1.5% by mass.
[0016] As a preferred solution, the binder is bentonite, and its TFe content is 2.0% to 3.5% by mass, and its SiO2 content is 50% to 56%. Preferably, bentonite is used as a binder, which can improve the molding performance and uniformity of the green balls, optimize their performance during drying and roasting, and by controlling the bentonite composition, the compressive strength and high temperature resistance of the balls can be further improved.
[0017] As a preferred solution, the conditions for blast drying are: temperature of 360°C to 500°C and time of 7min to 10min. The drying temperature and drying time are appropriately increased during blast drying, which can ensure that the green balls can still be fully dried without exhaust drying, avoiding the problem of surface sulfate enrichment caused by the adsorption of SO2 by undried green balls during the subsequent preheating process, thereby improving the quality and metallurgical properties of the pellets.
[0018] As a preferred solution, the conditions of preheating I are: temperature of 620°C to 700°C, and time of 3.0min to 4.0min. As a preferred solution, the conditions of preheating II are: temperature of 920°C to 950°C, and time of 4.0min to 5.5min. The temperature of preheating I and preheating II is increased step by step to avoid the explosion of pellets, and make sulfur dioxide mainly concentrated in preheating II emission. In particular, by accurately controlling the temperature and time of the preheating stage, it is ensured that the pellets are evenly heated before roasting, reducing the surface enrichment of SO2, and ensuring the high compressive strength and low reduction expansion rate of the finished pellets.
[0019] As a preferred solution, the calcination conditions are: temperature of 1250° C. to 1280° C. and time of 10 min to 20 min.
[0020] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:
[0021] 1) The desulfurizer provided by the present invention can increase the desulfurization efficiency of the pellets in the drying and preheating stage without reducing the iron grade of the pellets.
[0022] 2) The method for enhancing the desulfurization of high-sulfur iron ore concentrate pellets provided by the present invention can ensure that the raw pellets are heated evenly during the drying and preheating process by using a special desulfurizer, canceling the traditional exhaust drying design, and optimizing the conditions such as the blast drying and preheating temperature and time, thereby reducing the enrichment of SO2 on the surface, effectively improving the strength of the finished pellets, and reducing the impact of SO2 on equipment and the environment.
[0023] 3) The method for enhanced desulfurization of high-sulfur iron ore concentrate pellets provided by the present invention reduces equipment complexity and maintenance costs. At the same time, the operation process is easy to implement, has high production efficiency and economic benefits, and is suitable for large-scale industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the SEM spectrum of the preheated pellets prepared in Example 3 of the present invention; it can be seen from the figure that when the high-sulfur iron concentrate pellets use 1.5% desulfurizer and the exhaust drying stage is removed in the drying process, the S content element distribution in the pellets is relatively low, indicating that the preheated pellets are desulfurized more thoroughly, and only a small amount of S element is combined with the alkali metal and remains inside the preheated pellets.
[0025] Figure 2 This is the SEM spectrum of the preheated pellets prepared in Comparative Example 2 of the present invention. It can be seen from the figure that when the desulfurizer is added in an amount of 0.5%, it can be clearly seen that a large amount of S element is combined with Fe element, indicating that the oxidation decomposition efficiency of pyrite / pyrrhotite in the high-sulfur iron concentrate pellets is low. DETAILED DESCRIPTION
[0026] The following examples are intended to further illustrate the present invention, rather than to limit the scope of protection of the claims of the present invention.
[0027] In the following examples and comparative examples: the CaO2 reagent and MnO2 reagent can be purchased on the market with a purity of >98.8%. The Fe content of the direct reduced iron dust is 61%, and the SiO2 content is 2.3%; the mass proportion of the CaO2 reagent, MnO2 reagent and direct reduced iron dust particle size that meets the -10μm particle size is 93%. The composition of high-sulfur iron concentrate is TFe 64.34%, SiO2 1.65%, CaO 2.04%, MgO 1.64%, Al2O3 1.02%, S 0.84%, Na2O 0.09, K2O 0.10%, and the composition of bentonite is SiO2 55.95%, CaO 2.58%, MgO 0.41%, Al2O3 1.45%, Na2O 2.36%, K2O 0.74%, and TFe mass content is 3.0%.
[0028] In the following specific embodiments, the pellet heat treatment process adopts a chain grate-rotary kiln system, and the specific pellet production process is as follows: the desulfurizer, high-sulfur iron ore and bentonite are transported to the mixing bin by a belt, and after being fully mixed, the pellets are made in a disc pelletizer and the moisture content of the raw balls is controlled to 8% by adding water to obtain raw balls. Then, the raw balls enter the chain grate and pass through the blast drying section to obtain completely dried pellets. The dried pellets are directly preheated in preheating I and preheating II, and finally enter the rotary kiln for roasting.
[0029] Embodiment 1:
[0030] The weight ratio of high-sulfur iron concentrate, bentonite and desulfurizer (direct reduced iron powder dust: calcium peroxide powder: manganese dioxide powder = 90:7:3) is 97:2.0:1.0.
[0031] The temperature of the blast drying is 360°C and the time is 7 minutes.
[0032] The temperature of preheating I is 680°C and the time is 3 minutes.
[0033] The temperature of preheating II is 950°C and the time is 4.6 minutes.
[0034] The calcination temperature is 1260°C and the calcination time is 13 minutes.
[0035] The S content of the surface layer of the obtained preheated ball is 0.57%, the S content of the inner layer is 0.54%, the compressive strength of the finished pellet is 2400N, and the S content is 0.002%.
[0036] Embodiment 2:
[0037] The weight ratio of high-sulfur iron concentrate, bentonite and desulfurizer (direct reduced iron powder dust: calcium peroxide powder: manganese dioxide powder = 90:7:3) is 97:2.0:1.0.
[0038] The blast drying temperature was 420°C and the drying time was 7 minutes.
[0039] The temperature of preheating I is 660°C and the time is 3.5 minutes.
[0040] The temperature of preheating II is 940°C and the time is 5.0 min.
[0041] The calcination temperature is 1250°C and the calcination time is 15 min.
[0042] The S content of the surface layer of the obtained preheated pellets is 0.21%, the S content of the inner layer is 0.10%, the compressive strength of the finished pellets is 2550N, and the S content is 0.008%.
[0043] Embodiment 3:
[0044] High-sulfur iron concentrate, bentonite and desulfurizer (direct reduced iron powder dust: calcium peroxide powder: manganese dioxide powder = 85:10:5) are in a weight ratio of 96.5:2.0:1.5.
[0045] The temperature of the blast drying is 500°C and the time is 8 minutes.
[0046] The temperature of preheating I is 680°C and the time is 3 minutes.
[0047] The temperature of preheating II is 950°C and the time is 4.6 minutes.
[0048] The calcination temperature is 1260°C and the calcination time is 13 minutes.
[0049] The S content of the surface layer of the obtained preheated pellets is 0.20%, the S content of the inner layer is 0.24%, the compressive strength of the finished pellets is 2501N, and the S content is 0.013%.
[0050] Embodiment 4:
[0051] High-sulfur iron concentrate, bentonite and desulfurizer (direct reduced iron powder dust: calcium peroxide powder: manganese dioxide powder = 90:7:3) are in a weight ratio of 96:1.5:2.5.
[0052] The temperature of the blast drying is 450°C and the time is 10 minutes.
[0053] The temperature of preheating I is 680°C and the time is 3 minutes.
[0054] The temperature of preheating II is 950°C and the time is 4.6 minutes.
[0055] The calcination temperature is 1250°C and the calcination time is 20 min.
[0056] The S content of the surface layer of the obtained preheated pellets is 0.26%, the S content of the inner layer is 0.22%, the compressive strength of the finished pellets is 2446N, the S content is 0.015%, and the iron grade is 63.52%.
[0057] Comparative Example 1:
[0058] Compared with Example 1, the only difference is that: while adjusting the parameters of forced air drying, exhaust air drying is set. Specifically, the temperature of forced air drying is 310°C and the time is 3.4 minutes, the temperature of exhaust air drying is 400°C and the time is 5 minutes, and the hot air of exhaust air drying comes from the second preheating stage.
[0059] Other operations and control conditions refer to Example 1.
[0060] The S content of the surface layer of the preheated ball is 0.92%, the S content of the inner layer is 0.62%, the compressive strength of the finished pellet is 2100 N, and the S content is 0.015%.
[0061] Compared with Example 1, after adding the exhaust drying stage process, the sulfur content on the surface of the preheated pellets increased rapidly, and the pellet strength decreased by 300N, which was not conducive to the oxidation consolidation of the pellets.
[0062] Comparative Example 2:
[0063] The only difference from Example 2 is that the weight ratio of high-sulfur iron concentrate, bentonite and desulfurizer (direct reduced iron powder dust: calcium peroxide powder: manganese dioxide powder = 90:7:3) is 97.5:2.0:0.5. Other operations and conditions are controlled by reference to Example 2.
[0064] The S content of the surface layer of the obtained preheated pellets is 0.43%, the S content of the inner layer is 0.36%, the compressive strength of the finished pellets is 2294 N, and the S content is 0.012%.
[0065] Compared with Example 2, other process conditions are the same, except that the amount of desulfurizer added is reduced by 0.5%, the S content inside the preheated balls is increased by 0.26%, and the strength of the finished pellets is reduced by 256 N. Therefore, a low amount of desulfurizer added is not conducive to the desulfurization of the preheated balls and reduces the strength of the pellets.
[0066] Comparative Example 3:
[0067] The only difference from Example 3 is that the temperature of the blast drying section is 340°C and the time is 8 minutes. Other operations and conditions are controlled by reference to Example 3.
[0068] The sulfur content of the surface layer of the obtained preheated pellets was 0.46%, the sulfur content of the inner layer was 0.49%, the compressive strength of the finished pellets was 2265N, and the sulfur content was 0.016%. Compared with Example 3, after the drying temperature was reduced, the sulfur content of the inner layer of the preheated pellets increased by 0.25%, and the strength of the pellets decreased by 236N. The lower drying temperature is not conducive to the desulfurization of the pellets, resulting in delayed desulfurization and affecting the oxidation efficiency of the pellets.
[0069] Comparative Example 4:
[0070] The only difference from Example 4 is that the air drying temperature is 450°C and the time is 4 minutes. Other operations and conditions are controlled by reference to Example 4.
[0071] The S content of the surface layer of the obtained preheated pellets is 0.39%, the S content of the inner layer is 0.37%, the compressive strength of the finished pellets is 2187N, and the S content is 0.021%.
[0072] Compared with Example 4, after the blast drying time was shortened, the sulfur content in the inner layer of the preheated pellets increased by 0.15%, and the pellet strength decreased by 259 N. The shorter drying time reduced the desulfurization rate of the drying, resulting in rapid desulfurization in the preheating stage, which was not conducive to the oxidation consolidation of the pellets.
[0073] Comparative Example 5:
[0074] The only difference from Example 4 is that the high-sulfur iron concentrate, bentonite and desulfurizer (direct reduced iron powder dust: calcium peroxide powder: manganese dioxide powder = 80:15:5) are in a weight ratio of 96:1.5:2.5. Other operations and conditions are controlled in accordance with Example 4.
[0075] The S content of the surface layer of the obtained preheated pellets is 0.37%, the S content of the inner layer is 0.52%, the compressive strength of the finished pellets is 2237N, the S content is 0.015%, and the iron grade is 62.14%.
[0076] Compared with Example 4, the amount of reduced iron powder dust added to the desulfurizer was reduced, the inner sulfur content of the preheated pellets increased by 3.0%, the pellet strength decreased by 209N, and the iron grade decreased by 1.38%. The lower amount of reduced iron powder dust and the higher amount of calcium peroxide added to the desulfurizer affected the total iron content and oxidative consolidation in the pellets, resulting in a decrease in the iron grade and strength of the pellets.
Claims
1. A method for enhancing the desulfurization of high-sulfur iron ore concentrate pellets, characterized in that: The desulfurizer is mixed with sulfur-containing iron concentrate and a binder to form pellets, and the obtained green balls are sequentially subjected to blast drying, preheating I, preheating II and roasting by a chain grate-rotary kiln system to obtain finished pellets; The mass of the desulfurizer accounts for 1.0-2.5% of the total mass of the desulfurizer, the sulfur-containing iron concentrate and the binder; The conditions of the blast drying are: temperature of 360°C to 500°C, time of 7min to 10min; The preheating conditions are as follows: temperature is 620°C to 700°C, and time is 3.0min to 4.0min; The conditions of the preheating II are: temperature of 920°C to 950°C, time of 4.0min to 5.5min; The calcination conditions are: temperature of 1250°C to 1280°C, time of 10min to 20min; The desulfurizer is composed of the following components in percentage by mass: Direct reduced iron powder dust 85~93%; Calcium peroxide powder 5~10%; Manganese dioxide powder 2~5%.
2. The method for enhancing the desulfurization of high-sulfur iron ore concentrate pellets according to claim 1, characterized in that: The direct reduced iron powder dust has an Fe content of 50-80% by mass and an SiO2 content of 1.5-2.5% by mass.
3. The method for enhancing the desulfurization of high-sulfur iron ore concentrate pellets according to claim 1, characterized in that: The particle sizes of the direct reduced iron powder dust, the calcium peroxide powder and the manganese dioxide powder all satisfy that the mass proportion of the -10 μm particle size is more than 90%.
4. The method for enhancing the desulfurization of high-sulfur iron ore concentrate pellets according to claim 1, characterized in that: The binder is bentonite, and its TFe mass content is 2.0% to 3.5%, and its SiO2 content is 50% to 56%.
Citation Information
Patent Citations
High sulfide pyrite pellet reinforced roasting consolidation technology
CN102242254A
Sulfur fixation method of roasting low-grade molybdenite concentrate through lime method
CN105112647A